Pengurusan pemasaran syarikat penerbitan: satu kajian terhadap dua syarikat / Nurjannah Mohd Saleh - Mohd Saleh, Nurjannah (Faculty of Education, 2013)
The objective of this study is to identify the marketing management practices carried out by two private publications companies, Buku Fixi and Jemari Seni Sdn. Bhd. Both companies focus on a niche market and are consistent in terms of the genres of published books for the past few years. Both have different backgrounds and missions but producing the same product which are mainly novels. This study is based on the concept of marketing mix (the 4Ps) introduced by Jerome McCarthy which analyzes the elements of marketing and its related aspects. Qualitatif approach was used whereby interviews and library research were conducted. In general, the study found that the marketing practiced by both companies had resulted in different degrees of achievements. It can be concluded that an effective marketing strategy by the owners and managers in promoting their products will very much assist a company in reaching its goal and success.